Urgent-start dialysis in patients referred early to a nephrologist—the CKD-REIN prospective cohort study. Issue 8 (4th May 2021) - Fages, Victor; de Pinho, Natalia Alencar; Hamroun, Aghilès; Lange, Céline; Combe, Christian; Fouque, Denis; Frimat, Luc; Jacquelinet, Christian; Laville, Maurice; Ayav, Carole; Liabeuf, Sophie; Pecoits-Filho, Roberto; et al.
Abstract: Background: The lack of a well-designed prospective study of the determinants of urgent dialysis start led us to investigate its individual- and provider-related factors in patients seeing nephrologists. Methods: The Chronic Kidney Disease Renal Epidemiology and Information Network (CKD-REIN) is a prospective cohort study that included 3033 patients with CKD [mean age 67 years, 65% men, mean estimated glomerular filtration rate (eGFR) 32 mL/min/1.73 m 2 ] from 40 nationally representative nephrology clinics from 2013 to 2016 who were followed annually through 2020. Urgent-start dialysis was defined as that 'initiated imminently or <48 hours after presentation to correct life-threatening manifestations' according to the Kidney Disease: Improving Global Outcomes 2018 definition. Results: Over a 4-year (interquartile range 3.0–4.8) median follow-up, 541 patients initiated dialysis with a known start status and 86 (16%) were identified with urgent starts. The 5-year risks for the competing events of urgent and non-urgent dialysis start, pre-emptive transplantation and death were 4, 17, 3 and 15%, respectively. Fluid overload, electrolytic disorders, acute kidney injury and post-surgery kidney function worsening were the reasons most frequently reported for urgent-start dialysis. Adjusted odds ratios for urgent start were significantly higher in patients living alone {2.14 [95% confidence interval (CI) 1.08–4.25] or with low health literacy [2.22 (95% CI 1.28–3.84)], heart failure [2.60 (95% CI 1.47–4.57)] or hyperpolypharmacy [taking >10 drugs; 2.14 (95% CI 1.17–3.90)], but not with age or lower eGFR at initiation. They were lower in patients with planned dialysis modality [0.46 (95% CI 0.19–1.10)] and more nephrologist visits in the 12 months before dialysis [0.81 (95% CI 0.70–0.94)] for each visit. Conclusions: This study highlights several patient- and provider-level factors that are important to address to reduce the burden of urgent-start dialysis. Graphical Abstract: